ROLE OF NUCLEAR FACTOR NF-κB IN ALLOGRAFT REJEKTION - N. V. Kuncevich (Вестник трансплантологии и искусственных органов)
Nuclear factor kappa B (NF-κB) is a rapid response transcription factor for genes whose products are critical for inflammation and immunity. In this review structure and general properties of NF-κB the role of transcription factor NF-κB in allograft rejection are presented. In this review considered the mechanism activation of NF-κB in allograft rejection and its role in following pathological processes: endothelial cells activation, recipient T-cells activation and maturation of dendritic cells (antigen – presenting immune cells). NF-κB – targeted therapeutics approaches, that might be effective in transplantation are presented.